2019
DOI: 10.3390/agronomy9110743
|View full text |Cite
|
Sign up to set email alerts
|

The Growth and Development of Sweet Basil (Ocimum basilicum) and Bush Basil (Ocimum minimum) Grown under Three Light Regimes in a Controlled Environment

Abstract: Light is a crucial element for plant growth and production. In areas where natural light is not sufficient for optimal plant growth and production, high pressure sodium (HPS) light sources are widely used. However, HPS lamps are considered not very electrically efficient generating high radiant heat and as a consequence, there has been a lot of interest in replacing HPS lamps with new more efficient lighting sources in the form of light-emitting diodes (LEDs). The effects of three lighting sources (White LED, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 61 publications
5
10
2
Order By: Relevance
“…This also supports the current results concerning the significant impact of blue dominant treatment on stomatal conductance in basil. In an earlier publication (Aldarkazali et al [41]), we reported the significant impact of a high blue to red ratio on the stomatal conductance, leaf area, photosynthesis efficiency and yield parameters of basil, and this has been upheld in the current paper.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This also supports the current results concerning the significant impact of blue dominant treatment on stomatal conductance in basil. In an earlier publication (Aldarkazali et al [41]), we reported the significant impact of a high blue to red ratio on the stomatal conductance, leaf area, photosynthesis efficiency and yield parameters of basil, and this has been upheld in the current paper.…”
Section: Discussionsupporting
confidence: 55%
“…Maggie seeds were obtained from CN seeds (CN Seeds, Pymoor, Ely, Cambridgeshire, UK), were sown and were germinated in a glasshouse at Skardon gardens. Growing conditions were applied as reported previously [41]. Plants were harvested at full vegetative growth, pre-flowering.…”
Section: Absorption Spectrum Of Sweet Basil Between 300 and 700 Nmmentioning
confidence: 99%
“…With regard to the genetics, all plant samples were from the same species, as confirmed by the DNA analysis of S. limbata from different elevations, which was performed by one of the study authors at the Department of Plant Science at University of California, Davis, under the supervision of Professor Potter. The results of this study were compatible with other studies on Origanum majorana that also found the highest content of essential oil in the vegetative stage of the plant, and suggested the vegetative stage as the best to harvest O. majorana (Ahmad et al, 2018;Aldarkazali et al, 2019;Barragan Ferrer et al, 2016;Moghaddam et al, 2015;Roche et al, 2019;Sarmoum et al, 2019;Sellami et al, 2009;Zebib et al, 2015). Similar results were also found for the highest content of essential oils of Nepeta kotschyi (Nejad Habibvash et al, 2020) and Teucrium polium L. (Maizi et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…It was revealed that plant performance is strongly in uenced by various factors such as altitude, climate, soil, developmental stages, extraction and analysis methods, genetic factors, abiotic stresses, and slope and modeling techniques can predict these factors in other areas [24,25,26,27,28]. The results of the current study were compatible with other studies that found the highest content of essential oil of Origanum majorana in the vegetative stage, so they proposed the vegetative stage as the best stage to harvest Origanum majorana [29,30,31,32,33,34,35,36].Similar results were also found byon the essential oil content of Nepeta kotschyr [37]. Moreover, according to a study conducted by the highest yield of essential oil in Teucrium polium L. was obtained in the vegetative stage [38].…”
Section: Resultssupporting
confidence: 87%
“…Basil (Ocimum basilicum L.), is an important essential oil crop, medicinal plant and culinary herb, belongs to the Lamiaceae family, which grows in tropical and sub-tropical climates, [17][18][19][20][21][22][23][24] and its essential oil is a component of oral health, dental products, and has been used in the fragrance and food industry. [25] O basilicm, belongs to genus of Ocimum, family of Lamiacaea, order of Lamiales, class of Magnoliopsida, phylum of Magnoliopsida, and kingdom of plantae.…”
Section: Basil Occurrence Cultivation Classification and Variation mentioning
confidence: 99%